(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: This study aimed to establish quality standards for the aerial parts of the medicinal plant Iceland poppy (Papaver nudicaule L.). Methods: The anatomical structures of the aerial parts of plants were determined using microscopy. Bioactive compounds were identified and quantified using High-Performance Liquid Chromatography (HPLC). General quality parameters of the aerial parts of the Iceland poppy (Papaver nudicaule L.) were determined using the methods outlined in the European Pharmacopoeia. Results: The plant was collected from gravelly soil along the riverbank near the mouth of the Gorkhi-Terelj Valley in Erdene Soum, Tuv Province. The microstructure of the aerial parts of the Iceland poppy (Papaver nudicaule L.) was determined. The quality parameters of the aerial parts of Iceland poppy (Papaver nudicaule L.) were determined as follows: total ash content 5.54±0.2131%, moisture content 4.11±0.41%, and extractable substances with 70% ethanol were found to be highest at 27.61±0.43%. Additionally, the heavy metal and microbiological purity levels complied with the recommendations of the WHO and the requirements of the European Pharmacopoeia. Conclusion: The standardization criteria for the aerial parts of Papaver nudicaule L. were established. In addition, the pseudoprotopine alkaloid content in the aerial parts of Papaver nudicaule was found to be 0.0288 ± 0.0005%.